SYSTEMIC JUSTICE: SYSTEMIC AND FAMILY CONSTELLATION AS AN INNOVATION IN THE LEGAL FIELD - de Paula, Vanêssa Emanuela Marques; Dutra, Joyce da Cruz Ferraz; Azevedo, Vasco Ariston de Carvalho (Editora Impacto Científico, 2025)
This chapter analyzes the application of Systemic and Family Constellations (SFC) as an innovation in the legal field, proposing a notion of systemic justice—an approach that complements, but does not replace, positive law. Based on a triangular methodological design (an integrative literature review of 28 studies, qualitative and quantitative research with 131 Brazilian constellation practitioners, and an analysis of institutional case studies), the text demonstrates how the phenomenological-systemic principles of SFC—belonging, order, and balance in exchanges—allow for transgenerational access, symbolic exclusions, and unconscious loyalties that sustain seemingly insoluble conflicts. The analysis covers applications in judicial mediation, inheritance law, business disputes, and community justice, highlighting experiences at the CEJUSC-BH and the OAB Systemic Law Commissions. The chapter also addressed epistemological criticisms of SFC, reaffirming its phenomenological (non-positivist) nature and proposing rigorous ethical protocols—especially in sensitive contexts such as domestic violence. Finally, it discusses future trends, such as the training of "systemic legal facilitators," inclusive public policies, and the research agenda for a systemic science of justice, always with critical attention to the dimensions of gender, coloniality, and cultural diversity. Far from being a mystical practice or a substitute for the rule of law, CSF emerges as a sensitive social technology capable of humanizing justice and interrupting cycles of tragic reproduction. DOI: https://doi.org/10.56238/edimpacto2025.068-005